2016
DOI: 10.1038/ismej.2016.120
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and oceanic distribution of prasinophytes clade VII, the dominant group of green algae in oceanic waters

Abstract: Prasinophytes clade VII is a group of pico/nano-planktonic green algae (division Chlorophyta) for which numerous ribosomal RNA (rRNA) sequences have been retrieved from the marine environment in the last 15 years. A large number of strains have also been isolated but have not yet received a formal taxonomic description. A phylogenetic analysis of available strains using both the nuclear 18S and plastidial 16S rRNA genes demonstrates that this group composes at least 10 different clades: A1-A7 and B1-B3. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 81 publications
6
86
2
Order By: Relevance
“…S9A). BLAST analysis and alignment of Chlorophyta OTUs (data not shown) revealed that the V9 region of some Chlamydomonas is very similar to that of prasinophytes clade VII A5 (Lopes dos Santos et al ., ). Interestingly, the number of reads recovered in V4 and V9 for these 2 assignations (i.e., Chlamydomonas sp.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…S9A). BLAST analysis and alignment of Chlorophyta OTUs (data not shown) revealed that the V9 region of some Chlamydomonas is very similar to that of prasinophytes clade VII A5 (Lopes dos Santos et al ., ). Interestingly, the number of reads recovered in V4 and V9 for these 2 assignations (i.e., Chlamydomonas sp.…”
Section: Resultsmentioning
confidence: 97%
“…For Chlorophyta, average similarity is in general lower in V9 than V4 (Tragin et al ., ), which suggests that V9 will be more discriminating than V4 and will be the best choice. This is the case for example for prasinophytes clade VII, an important oceanic group, for which the use of 99% threshold for V9 OTUs allows to discriminate all sub‐clades defined to date (Lopes dos Santos et al ., ), while in V4, several clades collapse together, having identical sequences in that region. The V9 region of some Chlamydomonas is very similar to that of prasinophytes clade VII A5, which could lead to misinterpret the distribution of this specific sub‐clade when using the V9 region.…”
Section: Concluding Remarks – What Is the Best Choice: V4 Or V9?mentioning
confidence: 99%
“…Recent 18S V9 amplicon‐based studies (de Vargas et al ., ; Lopes Dos Santos et al ., ) cannot discriminate between Ostreococcus OI and OII (Monier et al ., ), or the two Bathycoccus , and have yet to be evaluated in the context of abundance data generated by quantitative methods. These amplicon data have been used to infer which green algal taxa dominate in the open ocean, specifically observing that Mamiellophyceae contribute only 1.8% of total photosynthetic sequences and that other prasinophytes, that have fourfold higher relative amplicon percentages, are therefore the dominant group (Lopes Dos Santos et al ., ). Here, we performed a quantitative enumeration of BI and BII and analysed these in the context of OI and OII abundances and eukaryotic phytoplankton cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained strains of several taxa that, to our knowledge, have not previously been cultured. Within prasinophyte clade VII, we obtained for the first time a representative of clade VIIB3 (Lopes dos Santos et al., ). In addition, three Pelagophyceae cultures corresponded to undescribed taxa.…”
Section: Discussionmentioning
confidence: 99%